2009
DOI: 10.1051/dst/2009002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of medium-concentration factor microfiltration treatment on the characteristics of low-moisture Mozzarella cheese

Abstract: -To study the chemical properties, the initial recovery of milk components, oiling off, and the textural properties of the cheese during a 60-day refrigerated storage period, skim milk was microfiltered through a 1.4-μm ceramic membrane to remove bacteria, and then low-moisture Mozzarella cheese was manufactured from medium-concentration factor (CF) microfiltration (MF) (0.1 μm of pore size, CF = 2.3) retentate with added cream. The changes in expressible serum (ES) were also studied. Three cheese-making trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(43 reference statements)
1
4
0
1
Order By: Relevance
“…All of the low-fat Mozzarella cheeses made during this research felt similar in firmness when manually examined, and slightly softer than a typical low-moisture part skimmed Mozzarella cheese. They did not have the hard rubbery texture that often occurs in low-fat cheeses (Awad et al 2005;Dong et al 2009) and matched fullfat Mozzarella cheese texture as reported by Bhaskaracharya and Shah (1999). This was attributed to the high moisture (52 to 53%) content and decreased calcium levels obtained by using direct acidification (Breene et al 1964;McMahon and Oberg, 2000).…”
Section: Texturesupporting
confidence: 49%
“…All of the low-fat Mozzarella cheeses made during this research felt similar in firmness when manually examined, and slightly softer than a typical low-moisture part skimmed Mozzarella cheese. They did not have the hard rubbery texture that often occurs in low-fat cheeses (Awad et al 2005;Dong et al 2009) and matched fullfat Mozzarella cheese texture as reported by Bhaskaracharya and Shah (1999). This was attributed to the high moisture (52 to 53%) content and decreased calcium levels obtained by using direct acidification (Breene et al 1964;McMahon and Oberg, 2000).…”
Section: Texturesupporting
confidence: 49%
“…There are only few reports describing functional properties of MF cheese; the functionality and structure have been investigated by ArdissonKorat and Rizvi (2004), Rizvi (2001a, 2001b), Dong, Chen, Maubois, and Ma (2009), Larsson (2004), Larsson, Zakora, Dejmek, and Ardö (2006), Nelson and Barbano (2005), Rudan (2002a, 2002b), O'Mahony, McSweeney, andLucey (2008), andSchafroth, Fragniere, andBachmann (2005). The physico-chemical characteristic of UF retentate was studied in some detail, e.g., by Bienvenue, JimenezFlores, and Singh (2003), Fox and McSweeney (1998), Karlsson (2005), and Velez-Ruiz and Barbosa-Canovas (2000), while the physico-chemical characteristics, including the rheology, of MF concentrate have still not been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, a remoção de microrganismos por membranas com diâmetro de poro de 1,4 µm não modifica a composição do leite microfiltrado (DONG et al, 2009;TOMASULA et al, 2011).…”
Section: Braz J Food Technolunclassified